Cross-Coupling Hydrogen Evolution Reaction in Homogeneous Solution without Noble Metals - Zhong, Jian-Ji; Meng, Qing-Yuan; Liu, Bin; Li, Xu-Bing; Gao, Xue-Wang; Lei, Tao; Wu, Cheng-Juan; Li, Zhi-Jun; Tung, Chen-Ho; Wu, Li-Zhu (Organic letters, 2014)
A highly efficient noble-metal-free homogeneous system for a cross-coupling hydrogen evolution (CCHE) reaction is developed. With cheap, earth-abundant eosin Y and molecular catalyst Co(dmgH)2Cl2, good to excellent yields for coupling reactions with a variety of isoquinolines and indole substrates and H2 have been achieved without any sacrificial oxidants. Mechanistic insights provide rich information on the effective, clean, and economic CCHE reaction.